General Authority Investigators And Prosecutors Perma After Entry Number 2 Of 2012 Concerning The Adjustment Of Limitations For Crime And Number Of Fines In Light Of The Criminal Code - Dany Bramandoko (Jurnal Daulat Hukum, 2018)
With the Perma No. 2 of 2012 then the misdemeanor case will be examined by a quick inspection event. The formulation of the problem and the purpose of this thesis is to describe and analyze the position of Supreme Court Regulation No. 2 of 2012 in the settlement of a misdemeanor, and to describe and analyze the implications of enforceability Perma No. 2 of 2012 against the authority of the investigators and prosecutors in cases of detention and the case investigation in court. This research method using normative legal research methods dengn type of research is descriptive analytical. Based on the analysis Perma No. 2 of 2012 to put forward the following results, that the legal position Perma No. 2 of 2012 is in substance related to the adjustment of the limits misdemeanor and fines in Perma No. 2 of 2012 which was ordered by higher laws or formed under the authority, in this case based on Article 79 of Act No. 5 of 2004 jo. Act No. 3 of 2009. The publication of Perma No. 2 of 2012 had an enormous impact on the implementation of the provisions of the detention authority possessed by the law enforcement agencies in the criminal justice process, especially in the judiciary under the authority of the Supreme Court. Of the offenses set out in the Supreme Court Regulation No. 2 of 2012 Section 1.Keywords: Investigators And Prosecution Authority, Perma No. 2 of 2012